Сократите дробь:
1) ах+ау-bx-by дробная черта ax-ay-bx+by
2) ab+ac+b^(2)+bc дробная черта ax+ay+bx+by
1)
2)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1)![\frac{ax+ay-bx-by}{ax-ay-bx+by}=\frac{a(x+y)-b(x+y)}{a(x-y)-b(x-y)}=\frac{(a-b)(x+y)}{(a-b)(x-y)}=\frac{x+y}{x-y} \frac{ax+ay-bx-by}{ax-ay-bx+by}=\frac{a(x+y)-b(x+y)}{a(x-y)-b(x-y)}=\frac{(a-b)(x+y)}{(a-b)(x-y)}=\frac{x+y}{x-y}](https://tex.z-dn.net/?f=%5Cfrac%7Bax%2Bay-bx-by%7D%7Bax-ay-bx%2Bby%7D%3D%5Cfrac%7Ba%28x%2By%29-b%28x%2By%29%7D%7Ba%28x-y%29-b%28x-y%29%7D%3D%5Cfrac%7B%28a-b%29%28x%2By%29%7D%7B%28a-b%29%28x-y%29%7D%3D%5Cfrac%7Bx%2By%7D%7Bx-y%7D)
2)![\frac{ab+ac+b^2+bc}{ax+ay+bx+by}=\frac{b(a+b)+c(a+b)}{a(x+y)+b(x+y)}=\frac{(a+b)(b+c)}{(x+y)(a+b)}=\frac{b+c}{x+y} \frac{ab+ac+b^2+bc}{ax+ay+bx+by}=\frac{b(a+b)+c(a+b)}{a(x+y)+b(x+y)}=\frac{(a+b)(b+c)}{(x+y)(a+b)}=\frac{b+c}{x+y}](https://tex.z-dn.net/?f=%5Cfrac%7Bab%2Bac%2Bb%5E2%2Bbc%7D%7Bax%2Bay%2Bbx%2Bby%7D%3D%5Cfrac%7Bb%28a%2Bb%29%2Bc%28a%2Bb%29%7D%7Ba%28x%2By%29%2Bb%28x%2By%29%7D%3D%5Cfrac%7B%28a%2Bb%29%28b%2Bc%29%7D%7B%28x%2By%29%28a%2Bb%29%7D%3D%5Cfrac%7Bb%2Bc%7D%7Bx%2By%7D)